Young children’s impressionable use of teleology: the influence of question wording and questioned topic on teleological explanations for natural phenomena - Halls, Jonathan; Ainsworth, Shaaron E.; Oliver, Mary (Taylor and Francis, 2018)
There is a significant body of research on children's preconceptions concerning scientific concepts and the impact this has upon their science education. One active issue concerns the extent to which young children's explanations for the existence of natural kinds rely on a teleological rationale: for example, rain is for watering the grass, or tigers’ stripes are for camouflage. It has been argued that this teleological tendency hampers children's ability to learn about causality in the natural world. This paper investigates two factors (question wording and topic) which it is argued have led to a misestimation of children's teleological tendencies within the area natural phenomena: i.e., those that are time-constrained, natural events or process such as snow, clouds or night. Sixty-six (5- to 8-years-old) children took part in a repeated-measures experiment, answering both open- and leading-questions across 10 topics of natural phenomena. The findings indicate that children's teleological reasoning may have been overestimated as open question forms significantly reduced their tendency to answer teleologically. Moreover, the concept of teleology is more nuanced than often suggested. Consequently, young children may be more able to learn about causal explanations for the existence of natural phenomena than the literature implies.